Penyuluhan Kesehatan Tentang Gizi pada Balita dan Anak Pra Sekolah di Desa Pukdale Kecamatan Kupang Timur Kabupaten Kupang - Brigita Dina Manek; Maria M.T Duka; Atalia Pili Mangngi; Avelina P Gusman; Deviserlina Babys (Natural: Jurnal Pelaksanaan Pengabdian Bergerak bersama Masyarakat., 2025)
Children are an investment in human resources (HR) that require special attention to the adequacy of their nutritional status from birth, even from the womb. Nutrients from food are the main source to meet the needs of children for optimal growth and development so that they can achieve complete health, namely physical, mental, and social health. This counseling activity was carried out in the Pukdale Village area, East Kupang District, Kupang Regency on Saturday, December 14, 2024, starting at 09.00 WITA. As the implementing staff are 4 supervisors of D-III Midwifery STIKes Maranatha Kupang. The number of mothers under five who participated in counseling was 30 mothers. This service activity began with the distribution of questionnaires (pre-test) before counseling, then the distribution of counseling leaflets and continued with counseling. The evaluation was carried out by providing a questionnaire (post-test) to evaluate the mother's knowledge. The evaluation was carried out when the counseling was completed, about 30 minutes after the counseling.